AN ANALYSIS OF SOCIAL CLASS IN JAMES DE MONACCO'S MOVIE "THE PURGE: ANARCHY" - Liupama, Anzari; Sunra, La; Nasta, Mardiyanah (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
The purpose of this study to analyze the social class in the movie “The Purge: Anarchy”. The movie was chosen because it contains allusions and depictions of social classes in America and as the background of the incident. This study uses qualitative analysis techniques with a case study approach. The data collected are the dialogues and actions of the characters in the movie "The Purge: Anarchy". The theory of social classes developed by experts such as Karl Marx (1848) and Max Weber (1978) are used as an analytical framework. This study found that there are two types of social class in society, namely the upper class which is called the bourgeoisie and the lower class which is called the proletarian. The existence of these classes is influenced by factors of power, money, and prestige. This research also reveals the relationship between the upper and lower classes which tend to have an exploitative nature and the relationship between the lower class itself with all its conflicts and problems.